Aplikasi Sistem Presensi Pegawai PT. Berkah Pena Ilmu dengan Metode Location Based Service (LBS) Berbasis Android Menggunakan Firebase - Ikhya Ulumudin; NM Faizah; Widyat Nurcahyo (Design Journal, 2023)
PT. Pena Berkah Ilmu is a medium-sized company engaged in Food & Beverage, social and humanitarian institutions, event organizers, travel and merchandise sales where this company still implements attendance methods such as signatures for employees. The attendance of each employee is recorded through the existing attendance system. However, in its implementation, sometimes there are some persons who do not attend or forget to attend. This results in the employee being considered absent. This desire arose because this company experienced difficulties in processing attendance information data, resulting in more and more hardcopy archives and making it difficult when the company's management intended to recap and re-collect data and employee attendance lists. This study uses the waterfall method which describes a systematic and sequential approach to software, starting with the specification of employee requirements, design, modeling, construction, delivery of the system to employees and complete software support that is produced. With this attendance application, it will be easier for employees to carry out attendance attendance even though they are outside the office and attendance data will later be stored in the database so that it will make it easier for the personnel department to be able to recapitulate employee data.